Whole Blood Gene Expression Associated With Clinical Biological Age. (14th July 2018) - Lin, Honghuang; Lunetta, Kathryn L; Zhao, Qiang; Mandaviya, Pooja R; Rong, Jian; Benjamin, Emelia J; Joehanes, Roby; Levy, Daniel; van Meurs, Joyce B J; Larson, Martin G; Murabito, Joanne M
Abstract: Background: Biologic age may better reflect an individual's rate of aging than chronologic age. Methods: We conducted a transcriptome-wide association study with biologic age estimated with clinical biomarkers, which included: systolic blood pressure, forced expiratory volume at 1 second (FEV1), total cholesterol, fasting glucose, C-reactive protein, and serum creatinine. We assessed the association between the difference between biologic age and chronologic age (∆age) and gene expression in whole blood measured using the Affymetrix Human Exon 1.0st Array. Results: Our discovery sample included 2, 163 participants from the Framingham Offspring cohort (mean age 67 ± 9 years, 55% women). A total of 481 genes were significantly associated with ∆age ( p < 2.8 × 10 −6 ). Among them, 415 genes were validated ( p < .05/481 = 1.0 × 10 −4 ) in 2, 946 participants from the Framingham Third Generation cohort (mean age 46 ± 9 years, 53% women). Many of the significant genes were involved in the ubiquitin-mediated proteolysis pathway. The replication in 414 Rotterdam Study participants (mean age 59 ± 8, 52% women) found 104 of 415 validated genes reached nominal significance ( p < .05). Conclusion: We identified and validated 415 genes associated with ∆age in a community-based cohort. Future functional characterization of the biologic age-related gene network may identify targets to test for interventions to delay aging in older adults.